Наукові основи технологій естерів вищих жирних кислот - Мельник, Юрій Романович (Національний університет "Львівська політехніка", 2021)
Дисертація присвячена розробленню наукових основ технології естерів вищих жирних кислот. Встановлено закономірності одержання естерів вищих жирних кислот трансестерифікацією тригліцеридів та естерифікацією вищих жирних кислот аліфатичними спиртами. Встановлено, що оксиди металів та іони металів, іммобілізовані на катіоніті КУ-2-8, у реакції трансестерифікації діють як гетерогенні каталізатори. Показано, що активність оксидів металів у реакції трансестерифікації зумовлена присутністю слабких кислотних центрів та зростає зі збільшенням поверхневої кислотності досліджених оксидів. Найвищу активність в реакції трансестерифікації виявляють каталізатори, які містять іони цинку, нікелю та олова. Встановлено оптимальні умови застосування досліджених каталізаторів та визначено вплив умов на технологічні показники процесу трансестерифікації, зокрема, конверсію тригліцеридів та питому продуктивність реактора. Досліджено закономірності естерифікації вищих жирних кислот сумішами спиртів. Запропоновано здійснювати екстрагування кислот соапстоку головною фракцією етилового спирту з подальшою естерифікацією отриманого екстракту при каталізі птолуенсульфокислотою. Показано можливість повторного використання запропонованих каталізаторів при трансестерифікації відпрацьованих та нерафінованих олій та застосування сумішей спиртів, зокрема головної фракції та сивушної олії. Здійснено дослідно-промислову апробацію результатів досліджень, зокрема одержання дослідної партії н-пропілових та етилових естерів вищих жирних кислот трансестерифікацією соняшникової олії. The dissertation is devoted to the development of scientific foundations and the technology of higher fatty acids esters. The regularities of higher fatty acids esters obtaining by triglycerides transesterification and higher fatty acids esterification with aliphatic alcohols have been established. It is found that metal oxides and cation exchange resin KU-2-8 with immobilized metal ions act in the reaction as heterogeneous catalysts. It is shown that the metal oxides activity in the transesterification reaction is due to the presence of weak acid sites and increases with an increase in the surface acidity of the investigated metal oxides. It is shown that the highest activity in the transesterification reaction is exhibited by catalysts containing ions of zinc, nickel and tin. The optimal conditions for the use of the investigated catalysts are established. The effect of conditions on the technological parameters of the transesterification process, in particular on the triglycerides conversion and the reactor specific productivity of higher fatty acids esters, is studied. The regularities of higher fatty acids esterification by alcohol mixtures have been investigated. It is proposed to carry out the acids extraction from the soapstock with the head fraction of ethyl alcohol, followed by esterification of obtained extract catalyzed with p-toluenesulfonic acid. The possibility of proposed catalysts using for the processing of used and unrefined vegetable oils, and alcohols mixtures, in particular the ethyl alcohol head fraction and fusel oil, is shown. The possibility of ethyl alcohol using with a water content of up to 10% is established. The industrial testing of research results has been carried out, in particular, obtaining a pilot batch of n-propyl and ethyl esters of higher fatty acids by sunflower oil transesterification. The possibility of re-use of metal oxides and cation exchange resin KU-2-8 with immobilized metal ions as the transesterification reaction catalysts is shown.
Научные основы технологий эфиров высших жирных кислот
Scientific foundations of higher fatty acids esters technologies
Keywords: естери вищих жирних кислот; спирти; каталізатор; оксиди металів; катіоніт; трансестерифікація; естерифікація; соапсток; эфиры высших жирных кислот; спирты; катализатор; оксиды металлов; катионит; переэтерификация; этерификация; соапсток; higher fatty acids esters; alcohols; catalyst; metal oxides; cation exchange resin; transesterification; esterification; soapstock; 66.094.942+66.095.132